A Drug‐Free Therapeutic System for Cancer Therapy by Diselenide‐Based Polymers Themselves. Issue 2 (25th October 2020) - Wei, Chao; Liang, Bingyu; Li, Yongsheng; Yan, Bingkun; Zhou, Yan; Liu, Yingbin; Lang, Meidong
Abstract: The application of nanotechnology‐based drug delivery systems has resulted in great progresses in cancer therapy. However, current systems ultimately depend on the action of the drug itself and almost all nanocarriers only serve as excipients without any therapeutic efficacy. Herein, a drug‐free therapeutic system is put forward, in which synthetic polymers themselves naturally exhibit effective anticancer activity without the loading of additional chemotherapy drugs. Aiming at this goal, amphiphilic poly(diselenide‐carbonate) copolymers (PSeSeTMC), consisting of monomethyl ether poly(ethylene glycol) and diselenide‐based polycarbonates, are designed and synthesized to build spherical nanoparticles, which show effective and broad‐spectrum anticancer activities against multiple cancer cell lines and high selectivity toward cancer cells. Moreover, the anticancer activities can be well controlled by tuning the selenium contents in polymers. Mechanistic investigations indicate that PSeSeTMC can selectively induce cancer cells to express excessive reactive oxygen species, thereby leading to significant cellular apoptosis. In vivo antitumor studies further demonstrate high therapeutic efficacy and low side effects on normal tissue. Overall, this work provides a novel approach for cancer therapy by utilizing carriers themselves. Considering the fabrication process is pretty simple, this diselenide‐based polymeric system has great potential in clinical translation. Abstract : A drug‐free therapeutic system is put forward and designed for cancer therapy, in which synthetic amphiphilic poly(diselenide‐carbonate) (PSeSeTMC) polymers themselves naturally exhibit effective anticancer activity without the loading of additional chemotherapy drugs. In vitro and vivo experiments demonstrate that PSeSeTMC themselves exhibit obvious inhibition of tumor growth and minimal side effects.